2015
DOI: 10.1021/bm5017805
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Polymer Micelle/Clay Nanodisk/Doxorubicin Hybrid Injectable Gels for Safe and Efficient Focal Treatment of Cancer

Abstract: The purpose of this study was to fabricate a safe and effective doxorubicin (DOX)-delivery system for focal cancer chemotherapy. A novel biodegradable injectable gel was developed through self-assembly of poly(D,L-lactide-co-glycolide)-b-poly(ethylene glycol)-b-poly(D,L-lactide-co-glycolide) (PLGA-PEG-PLGA) copolymer micelles, clay nanodisks (CNDs), and DOX. We discovered that DOX loaded in the hybrid gels acts as an anticancer drug and as a building block to organize new gel networks. Accordingly, long-term s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…Hydrogels are 3-dimensionally interconnected hydrophilic polymers, which can absorb an extensive amount of water within the structures without being dissolved in water. Since the chemical, electrical, and mechanical properties of polymer hydrogels could be quite analogous with those present in biological tissues, there have been extensive efforts to utilize the hydrogels in biological applications such as drug delivery (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), wound/burn dressing (13,14), scaffolds for tissue engineering (15)(16)(17), and others (18)(19)(20)(21). In particular, the inclusion of drugs inside polymer hydrogels may represent an innovative drug delivery system because the release rate of the loaded drugs can be regulated by external stimuli (1,2,(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels are 3-dimensionally interconnected hydrophilic polymers, which can absorb an extensive amount of water within the structures without being dissolved in water. Since the chemical, electrical, and mechanical properties of polymer hydrogels could be quite analogous with those present in biological tissues, there have been extensive efforts to utilize the hydrogels in biological applications such as drug delivery (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), wound/burn dressing (13,14), scaffolds for tissue engineering (15)(16)(17), and others (18)(19)(20)(21). In particular, the inclusion of drugs inside polymer hydrogels may represent an innovative drug delivery system because the release rate of the loaded drugs can be regulated by external stimuli (1,2,(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the change in pH (2,3), temperature (1,7,9), and light (4) has triggered the swelling, shrinkage, or degradation of the hydrogels to release the drugs in a controlled way. Alternatively, in the absence of the external stimuli, the slow diffusion nature of the drug release can ensure a constant delivery as well as prolonged duration of drugs, which is necessary for exerting long-term efficacy (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, fewer cells with normal nuclei morphology were observed in the group treated with DTX/XNMs in comparison with cells treated with DTX/NNMs or DTX/LNMs, which, qualitatively, certified that DTX/XNMs could promote the apoptotic progress of A2780 cells. 45 …”
mentioning
confidence: 99%
“…We also revealed excellent cell compatibility from hemolysis assay and cell culture test on and in the hydrogels. Then, in 2015, Nagahama et al reported on a delivery system for DOX from thermoresponsive nanocomposite hydrogels (Figure 7b) [65], revealing that DOX worked as a crosslinking agent. They also revealed that long-term sustained release of DOX from thermoresponsive nanocomposite hydrogels without initial burst release could be achieved.…”
Section: Thermoresponsive Nanocomposite Hydrogels Composed Of Laponitmentioning
confidence: 99%